Identification and characterization of older emergency department patients with high‐risk alcohol use - Christina L. Shenvi; Mark A. Weaver; Kevin J. Biese; Yushan Wang; Rishab Revankar; Yetunde Fatade; Aileen Aylward; Jan Busby‐Whitehead; Timothy F. Platts‐Mills; Gail D'Onofrio (Journal of the American College of Emergency Physicians Open)
Abstract Background High‐risk alcohol use in the elderly is a common but underrecognized problem. We tested a brief screening instrument to identify high‐risk individuals. Methods This was a prospective, cross‐sectional study conducted at a single emergency department. High‐risk alcohol use was defined by National Institute on Alcohol Abuse and Alcoholism (NIAAA) guidelines as >7 drinks/week or >3 drinks/occasion. We assessed alcohol use in patients aged ≥ 65 years using the timeline follow back (TLFB) method as a reference standard and a new, 2‐question screener based on NIAAA guidelines. The Alcohol Use Disorders Identification Test (AUDIT) and Cut down, Annoyed, Guilty, Eye‐opener (CAGE) screens were used for comparison. We collected demographic information from a convenience sample of high‐ and low‐risk drinkers. Results We screened 2250 older adults and 180 (8%) met criteria for high‐risk use. Ninety‐eight high‐risk and 124 low‐risk individuals were enrolled. The 2‐question screener had sensitivity of 98% (95% CI, 93%–100%) and specificity of 87% (95% CI, 80%–92%) using TLFB as the reference. It had higher sensitivity than the AUDIT or CAGE tools. The high‐risk group was predominantly male (65% vs 35%, P < 0.001). They drank a median of 14 drinks per week across all ages from 65 to 92. They had higher rates of prior substance use treatment (17% vs 2%, P < 0.001) and current tobacco use (24% vs 9%, P = 0.004). Conclusion A rapid, 2‐question screener can identify high‐risk drinkers with higher sensitivity than AUDIT or CAGE screening. It could be used in concert with more specific questionnaires to guide treatment.